The Relationship Between Learning Styles, Creative Thinking Performance and Multimedia Learning Materials - Hafizoah, Kassim (Elsevier Ltd., 2013)
This paper reports the findings of a research which looks at the influence of learning styles on engineering students’ creative thinking performance when multimedia learning tool is used. Taking into consideration the ubiquity of technology-based educational tool and its possible impact on students’ creative performance, a multimedia learning tool was developed for a group of mechanical engineering students based on a specific subject. The purpose was to investigate the relationship between students’ learning styles and their creative thinking after using the multimedia learning tool. The Torrance Test of Creative Thinking (TTCT) was used as the main instrument to measure students’ creative thinking before and after the multimedia learning tool was administered. The Index of Learning Style (ILS) was also used to identify students’ learning styles. The independent sample t- test and one-way analysis of variance were used to compare the TTCT scores with the learning styles dimensions. The findings indicate that active, reflective, intuitive and high visual students benefit creatively after using the multimedia learning tool.